Above suspicion [videorecording (DVD)] - Thorpe, Richard, 1896-1991; MacMurray, Fred, 1908-1991; Crawford, Joan, 1908-1977; MacInnes, Helen, 1907-1985 (Archive collection., 2010)
Two American honeymooners in pre-war Europe are asked by British intelligence to help track down a missing agent.